Opening up food sovereignty and Community Supported Agriculture with organizational perspectives: zooming into the diversity of economic actors that are striving for food sovereignty - Middendorf, Matthias; Justus Liebig University Giessen (My University, 2025)
Agri-food systems face multiple interlinked crises, including accelerating climate change, biodiversity loss, entrenched social inequalities, and pressures on democratic institutions. Food sovereignty has emerged as a prominent pathway for transforming agri-food systems toward greater justice and sustainability, understood as peoples’ right to healthy, culturally appropriate food produced sustainably and to define their own agri-food systems. It is articulated as both a social movement and an alternative food concept and is addressed in movement strategies, policy debates, and research at international, national, and regional levels. Yet most analyses remain concentrated at the macro-/system-level, while actors and organizational phenomena receive limited analytical attention. In particular, actors engaged in economic activities (e.g., production, processing, distribution) are not consistently named in the food sovereignty discourse as ‘economic actors’ and are often overlooked. This stands in tension with the movement’s explicit calls to build an alternative economic model. Shaped by critiques of the corporate agri-food system, such terminological caution fosters generalization and limits differentiation among actors, thereby sidelining analysis at the organizational level. As a result, the organizational configurations through which economic actors operate (understood as combinations of organizational characteristics such as decision-making, property, and labor) are seldom examined. This conceptual flattening marginalizes organizational perspectives in the food sovereignty discourse and underrepresents the diversity of economic actors, their configurations, and challenges, thereby limiting opportunities for their support. The functioning and stability of economic actors are essential for shaping transformations. Accordingly, organizational configurations must be analyzed alongside economic activities. Community Supported Agriculture (CSA) organizations, often cited as an expression of food sovereignty, illustrate this gap, as they are rarely differentiated or subjected to organizational analysis. The overall aim of this dissertation is to open up, broaden, and deepen the discourse on food sovereignty and CSA by approaching food sovereignty not only as a movement and concept but also as an organizational phenomenon. It uses organizational perspectives as a heuristic lens to render the organizational configurations of economic actors analytically visible. Adopting an actor-centered perspective at the organizational level, the dissertation conceptualizes the diversity of economic actors striving for food sovereignty (EAFS) and differentiates their organizational configurations in general and for CSAs in particular. The first paper develops a conceptual framework based on an integrative literature review and thematic analysis of 108 publications on food sovereignty, including gray literature. It conceptualizes organizational diversity within EAFS by identifying general patterns across Global North and Global South contexts and differentiates EAFS at the organizational level. The second transdisciplinary paper develops a CSA Framework in partnership with the German CSA Network and applies a mixed-methods design to CSAs in Germany. It uses a survey of 70 CSAs to test the framework, documents organizational heterogeneity, demonstrates that configurations differ by governance type (producer-led, consumer-led, integrated), and confirms the diversity and complexity of CSA organizations. Synthesizing the findings of both studies yields the Synthesized EAFS Framework, which provides a more differentiated organizational perspective on EAFS. This framework distinguishes three domains comprising 12 characteristics: Conditions that shape EAFS (Motives, Transformative approach, Intersectionality), Organizational-related characteristics (Organizational governance types, Founding impulse and establishing paths, Ownership/Property and legal forms, Work/Labor, Participation, Non-economic partnerships and cooperation), and Economic-related characteristics (Production practices and services, Scope of supply chains, Economic partnerships and cooperation). The framework defines Size as a cross-cutting structural factor. Conditions guide configuration choices across these characteristics. The framework also embeds the governance typology from the second study as a key lever for allocating decision rights. In doing so, the framework provides an actor-centered language for systematic comparison that moves beyond overly abstract descriptions. Finally, the dissertation aligns the Synthesized EAFS Framework with the six food sovereignty pillars established at the 1st Global Nyéléni Forum. This alignment makes configurations of EAFS at the organizational level analytically visible and grounds the framework in widely recognized movement principles. This supports the view that food sovereignty is also an organizational phenomenon and frames EAFS as a configuration space in which mixed forms are common. Accordingly, the findings reject simplistic binaries and show the prevalence of mixed forms: depending on the configuration, EAFS can combine conventional logics (e.g., market participation, revenue generation) with alternative approaches (e.g., solidarity-based practices, community ownership, collective governance, shared economic risk). This perspective centers on differentiated organizational configurations rather than generalized forms. Taken together, the dissertation makes several key contributions. Conceptually, it first makes the diversity of EAFS along the agri-food supply chain visible. Second, it develops an integrative, actor-centered organizational language and a novel framework that links food sovereignty goals to organizational phenomena and enables application across contexts as well as the analysis of EAFS configurations. Empirically, it documents organizational heterogeneity among CSAs in Germany, a prominent EAFS case, and shows how governance types and characteristics are distributed. Methodologically, it offers an analytical lens for comparing EAFS in different settings by making organizational configurations analytically visible. In practice, it guides context-sensitive configurations for practitioners and movement educators and supports alliance-building among EAFS. It enables the identification of organizational challenges (e.g., unclear decision rights and roles, resource constraints, power asymmetries) that provide a basis for strengthening organizational stability and adaptability. For policy and support systems, it points to the importance of aligning instruments with actual configuration options and addressing organizational challenges where relevant. Future research should refine and extend the Synthesized EAFS Framework beyond CSA to other EAFS (e.g., food hubs or food processing actors) and apply it across contexts, including in the Global South. It should examine decision-making, participation, and power within governance types to determine who benefits and who is excluded. It should also analyze how organizational stability and adaptability relate to governance and ownership/property under operational constraints. Overall, these directions shift the discourse from whether EAFS matter to how specific configurations function, for whom, and under what conditions, while supporting practice-research transfer within the contemporary food sovereignty discourse.
Öffnung von Ernährungssouveränität und Solidarischer Landwirtschaft mit organisationalen Perspektiven: Fokussierung auf die Vielfalt der Wirtschaftsakteure, die sich für Ernährungssouveränität einsetzen
Keywords: food sovereignty; Community Supported Agriculture; CSA; organizational perspective; organizational level; organizational perspective; organizational level; economic actor; Ernährungssouveränität; Solidarische Landwirtschaft; Solawi; Organisationale Perspektive; Wirtschaftsakteure; alternative organizations; Alternative Organisationen; diverse food economies; food system transformation; typology; Typologie; organizational governance; alternative food networks; Alternative Lebensmittelnetzwerke; ddc:000; ddc:300; ddc:330; ddc:630; ddc:650